Goddess girls Pheme the gossip - Holub Joan; Suzanne Williams (New York Simon & Schuster)
Pheme, the gossip-loving student at Mount Olympus Academy, faces consequences after snooping into Athena$1 (Bs diary, resulting in a "red-handed" curse.s
English